2021
DOI: 10.29045/14784726.2021.6.6.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic independent prescribing: a qualitative study of early adopters in the UK

Abstract: Background: Paramedics working in advanced practice roles in the UK can now train to prescribe medicine. This is anticipated to benefit patient access to medicines and quality of care where there is a national shortage of doctors, particularly in primary care.Aim: To explore the experience of paramedics who are early adopters of independent prescribing in a range of healthcare settings in the UK.Design and setting: A qualitative study involving interviews between May and August 2019, with paramedics in the UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This progression is also further recognition of the meaningful contribution paramedics make within contemporary healthcare systems and the increasingly complex and autonomous nature of their practice. 8,9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This progression is also further recognition of the meaningful contribution paramedics make within contemporary healthcare systems and the increasingly complex and autonomous nature of their practice. 8,9…”
Section: Introductionmentioning
confidence: 99%
“…This progression is also further recognition of the meaningful contribution paramedics make within contemporary healthcare systems and the increasingly complex and autonomous nature of their practice. 8,9 In Australia and New Zealand, referred to hereafter in this paper as Australasia, tertiary-level entry-to-practice education has been established for more than a quarter of a century. 10 The first Australasian tertiary programs emerged in 1994 as non-mandatory courses, taught largely as off-campus distance education hybrid offerings delivered in partnership with jurisdictional ambulance services, and staffed predominantly by ambulance industry educators in the absence of a paramedicine academic workforce.…”
Section: Introductionmentioning
confidence: 99%
“…In the decade since the introduction of independent prescribing, much of the literature has focused on the uptake of prescribing by AHP practitioners within each profession, alongside the evaluation and impact of its initial implementation [14][15][16][17][18][19][20]. Some papers have examined specific obstacles to independent prescribing within allied health [21,22], whilst others have focused on specific medicines used or conditions treated [23][24][25].…”
Section: Background and Contextmentioning
confidence: 99%
“…A systematic review of non‐medical prescribing by nursing staff identified significant advantages including the time and cost savings for the health service (Bhanbhro et al., 2011) and improved service responsiveness and efficiency (Courtenay et al., 2011; Graham‐Clarke et al., 2018; Hobson et al., 2010), while maintaining the quality and safety of medication management (Gielen et al., 2014). Non‐medical prescribing has also been proposed to improve professional autonomy (Armstrong, 2015; Armstrong et al., 2021; Bowskill, 2009; Carey et al., 2014; Cousins & Donnell, 2012; Downer & Shepherd, 2010; Graham‐Clarke et al., 2018; Stenner & Courtenay, 2008), improve job satisfaction (Armstrong et al., 2021; Bowskill, 2009; Carey et al., 2014; Cousins & Donnell, 2012; Downer & Shepherd, 2010; Graham‐Clarke et al., 2018; Green & Courtney, 2008; Hill et al., 2014; Stenner & Courtenay, 2008), support professional development (Adigwe, 2012; Graham‐Clarke et al., 2018; Stenner & Courtenay, 2008; Stenner et al., 2021) and improve service capacity (Stenner et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While non-medical prescribing by nursing continues to grow in acceptance and evidence base, Allied Health Practitioner (AHP) prescribing is a relatively new concept. Internationally and within Australia podiatrists, optometrists, paramedics and physiotherapists are among the growing group of AHPs with increasing legal rights to conduct prescribing under various models (Borthwick et al, 2010;Cooper, 2006;Department of Health, 2005, 2006b, Emmerton et al, 2005Graham-Clarke et al, 2019;Noblet et al, 2020;Stenner et al, 2021). There are many variations in AHP prescribing models implemented to date, depending on which component of the medi-cation management cycle the AHP is performing.…”
Section: Introductionmentioning
confidence: 99%